Phenotypic changes of auditory nerve fibers after excitotoxicity - Artem Diuba; Paul Gratias; Penelope W. C. Jeffers; Régis Nouvian; Jean-Luc Puel; Sharon G. Kujawa; Jérôme Bourien (Proceedings of the National Academy of Sciences, 2025)
There is a substantial body of evidence elucidating the pathophysiological aspects of excitotoxicity in the mammalian cochlea. However, the question of whether the resultant damage is reversible remains unresolved. To replicate an excitotoxic event, we investigated the long-term effects of kainate application in gerbil cochleae. Surprisingly, despite persistent synapse loss, the compound action potential of the auditory nerve fully recovered. This functional retrieval was associated with a phenotypic change in auditory nerve fibers. Thresholds were improved along the tonotopic axis. High-spontaneous rate (SR) fibers largely populated the apical region, while low-SR fibers from the basal region exhibited sound-driven activity indistinguishable from control high-SR fibers. This functional phenotype change may support the full recovery of neural response thresholds and amplitudes after excitotoxicity. Furthermore, hyperresponsiveness of the auditory nerve fibers could be a crucial factor in the development of hyperactivity in the central auditory pathways, a common occurrence following acoustic overstimulation.